Knee valgus angle during landing tasks in female volleyball and basketball players - Herrington, L. (The Journal of Strength and Conditioning Research, 2011)
Increased knee valgus angles have been associated with an increased risk of a variety of knee injuries. It has yet to be established if knee valgus angles during jump landing tasks differ between jumping sports with relatively higher and lower knee injury rates-namely, basketball and volleyball. Any difference in knee angles on landing may be related to sport-specific differences, which may in turn relate to the different injury risk rates. Fifteen elite female basketball and volleyball players had their knee valgus angles assessed during 2 landing tasks: 1 bilateral (drop jump landing) and 1 unilateral (step landing task). During the drop jump task knee valgus angle was significantly greater in the basketball group (p = 0.017) in the right knee, but there was no significant difference in performance between sports in the left knee (p = 0.67). During the step landing task volleyball players had significantly greater knee valgus angles than basketball players for both the left (p = 0.018) and right (p = 0.025) knees. The basketball group showed superior control of knee valgus during the unilateral task, which may be related to sport-specific skills. The basketball players showed significant asymmetry in knee valgus angle during bilateral drop jump landings; this finding reflects those of previous studies and may be related to the relative increased knee injury risk reported for this population group